An open-source testbed based on the modbus protocol for cybersecurity analysis of nuclear power plants - Brito, Israel Barbosa de (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.